2010
DOI: 10.1007/s10620-010-1442-8
|View full text |Cite
|
Sign up to set email alerts
|

Race and Inflammatory Bowel Disease in an Urban Healthcare System

Abstract: BackgroundInflammatory bowel disease (IBD) is increasingly common among non-Caucasian populations, but interracial differences in disease characteristics and management are not well-characterized.AimsWe tested the hypothesis that disease characteristics and management vary by race among IBD patients in an ethnically diverse healthcare system.MethodsA retrospective study of the safety net healthcare system of San Francisco, CA, from 1996 to 2009 was undertaken. Patient records with International Classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 29 publications
1
34
1
4
Order By: Relevance
“…Differences in UC disease extent and upper gastrointestinal CD involvement have each been shown in a single study, but other studies, including ours, have not redemonstrated these differences [1, 7, 12, 13, 15]. In addition, we identified differences in IBD extraintestinal manifestations in AA patients compared to Ca patients in both our UC and CD populations, which is similar with what has been reported in previous studies [7, 8].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Differences in UC disease extent and upper gastrointestinal CD involvement have each been shown in a single study, but other studies, including ours, have not redemonstrated these differences [1, 7, 12, 13, 15]. In addition, we identified differences in IBD extraintestinal manifestations in AA patients compared to Ca patients in both our UC and CD populations, which is similar with what has been reported in previous studies [7, 8].…”
Section: Discussionsupporting
confidence: 91%
“…While there is less data regarding differences in disease extent by race in patients with ulcerative colitis (UC), Moore et al [12] recently reported increased distal colitis and less pancolitis in AA patients with UC. In contrast, two recent comparably sized studies found no significant differences in disease location by race for either UC or CD [1, 13]. In agreement, a systematic review by Mahid et al [9] found that the overall evidence suggests that AA patients with IBD have similar symptoms, extraintestinal manifestations, disease location, and behavior to Ca patients.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations